2019
DOI: 10.1017/jfm.2019.121
|View full text |Cite
|
Sign up to set email alerts
|

Inclined slow acoustic waves incident to stagnation point probes in supersonic flow

Abstract: Tunnel noise in supersonic testing facilities is known to be a decisive factor in boundary layer transition experiments. It defines initial conditions for the growth of modal instabilities by the receptivity mechanism. That is, to interpret experimental results, the determination of tunnel noise is of crucial importance. It is common to use stagnation point probes equipped with pressure transducers in supersonic flows, but since tunnel noise undergoes modulation during the measurement, the probes must be calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…ZFS is a highly efficient multi-physics simulation framework and developed by the numerical group of the Institute of Aerodynamics and Chair of Fluid Mechanics (AIA), RWTH Aachen University. Flows with shocks were computed for several applications, i.e., a transonic airfoil in [43], a cone in supersonic flow in [48], a blunt stagnation point probe in supersonic flow in [46,47], and a reentry capsule in supersonic flow in [49].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ZFS is a highly efficient multi-physics simulation framework and developed by the numerical group of the Institute of Aerodynamics and Chair of Fluid Mechanics (AIA), RWTH Aachen University. Flows with shocks were computed for several applications, i.e., a transonic airfoil in [43], a cone in supersonic flow in [48], a blunt stagnation point probe in supersonic flow in [46,47], and a reentry capsule in supersonic flow in [49].…”
Section: Methodsmentioning
confidence: 99%
“…Three steps are required to obtain the full tangent (v, ฮพ) from the numerical simulation. First, the CFD code is modified to solve the additional equation for the shock location (47). Second, the modified method is enhanced by AD to yield the first component of the tangent v, i.e., the numerical discretization of equation (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous studies found the post-shock pressure-based turbulence intensity measured with pitot probes to vary as much as 300% between plateau #1 and #2 [32]. Both discrepancies can be explained by bow shock receptivity, or bow shock transfer functions, which vary significantly with the inclination angle of the disturbance [52][53][54] and were not applied to the data reported previously [32]. To investigate the inclination angles of the freestream disturbances, we will use correlations between signals in the two-dimensional FLDI array.…”
Section: Freestream Disturbancesmentioning
confidence: 95%
“…The definition of ๐œƒ ๐‘› is chosen to be consistent with the definitions used by others [50,[52][53][54] for backwards facing slow acoustic waves. The spanwise convection velocity, ๐‘ฃ ๐‘ , is assumed negligible in the following analysis.…”
Section: Freestream Disturbancesmentioning
confidence: 99%